Appearance of peripheral blood plasma cells and memory B cells in a primary and secondary immune response in humans. - Blanchard-Rohner, G; Pulickal, A; Jol-van der Zijde, C; Snape, MD; Pollard, A (2009)
In humans, the kinetics of the appearance of memory B cells and plasma cells during primary immunization are not well defined. In this study, we assessed the primary B-cell response of rabies-antigen naive volunteers during a 3-dose course of rabies vaccine compared with the B-cell response to a booster dose of rabies vaccine given to previously immunized volunteers. After a single dose of vaccine, in the naive group plasma and memory B cells appeared later (peak at day 10) than in the primed group (peak at day 7) and were at lower frequency. The most rapid responses (day 4) were detected after a third immunization in the naive group. This is the first study to document the detailed kinetics of the plasma cell and memory B-cell responses to immunization in adult humans and to demonstrate differences in the responses that relate to the preexisting immune status of the persons.